Multicultural Education Practices and Socio-Religious Values: The Study of Trans-Dalam Community in Central Kalimantan of Indonesia - Qodir, Abdul (Al-Albab, 2018)
This article describes the practice of multiculturalism education among local migrant communities with Trans-Dalam community in Pulang Pisau regency, Kalimantan Tengah province, Indonesia, as its focus of analysis. It asks the question about how Trans-Dalam community members with diverse social and religious backgrounds develop multicultural practices in their daily lives. The required data were collected through in-depth interviews and observation. This article argues that Trans-Dalam villagers preserve and conduct multicultural ideas and practices as seen in their day-to-day harmonious communal life due to their shared local values and wisdom. Inspired by their own expressions of shared social-religious values, each community of different ethnic background develops these multicultural practices, which are closely connected to their need for security as settlers with diverse social-cultural backgrounds that make them aware of the importance of living in harmony, mutual respect, and solidarity regardless of their differences in ethnicity, place of origin or religion.